Carrier type change induced by fluorine doping in spin-chain compound Ca3Co2O6. Issue 5 (12th January 2017) - Song, Jiyue; Zhao, Bangchuan; Huang, Yanan; Qin, Yanfeng; Zhou, Jiafeng; Song, Wenhai; Sun, Yuping
Abstract : Temperature dependence of thermopower for Ca3 Co2 O6− x F x . Abstract : The structural, magnetic, electrical, and thermoelectric properties of fluorine (F)-doped Ca3 Co2 O6 were investigated systematically. Based on the use of X-ray diffraction, X-ray photoelectron spectroscopy spectra, and magnetic data, it was concluded that part of the Co 3+ ions at octahedral sites would transfer into Co 2+ because of the substitution of F − for O 2− . The induced Co 2+ ions are antiferromagnetically coupled with the nearest neighboring Co 3+ . The room-temperature resistivity decreases monotonously with the increase of fluorine (F)-doping content, x, and it is suggested that this is related to the increased carrier mobility. The resistivity curves of the samples with x ≥ 0.4 show an anomaly at T * ∼ 320 K, which is considered to be related to the change of activation energy ( E a ). The room temperature thermopower S 300 K changed from a positive value of 686.6 μV K −1 to a negative value of −333.1 μV K −1 as x increases from 0 to 0.4 and considering this with the Hall coefficient result, it is concluded that suitable F-doping in Ca3 Co2 O6 can change the type of the majority of carriers from p to n with a decreased resistivity. The thermal conductivity, κ of the n-type samples is much larger than that of the p-type, and the κ of both the p-type and n-type samples decreases monotonously with increasing x . The anomaly of κ near x = 0.4 is suggested to originate from the decreased grain boundary scattering and the sudden decrease of E a at the critical point of the carrier type change.